2016
DOI: 10.1038/srep34879
|View full text |Cite|
|
Sign up to set email alerts
|

Nanoimaging granule dynamics and subcellular structures in activated mast cells using soft X-ray tomography

Abstract: Mast cells play an important role in allergic responses. During activation, these cells undergo degranulation, a process by which various kinds of mediators stored in the granules are released. Granule homeostasis in mast cells has mainly been studied by electron microscopy (EM), where the fine structures of subcellular organelles are partially destroyed during sample preparation. Migration and fusion of granules have not been studied in detail in three dimensions (3D) in unmodified samples. Here, we utilized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…To date, optical imaging techniques such as confocal laser endomicroscopy (CLE) or ultrastructural methods such as transmission electron microscopy (TEM) have been available for visualizing microstructures in 3D on micrometer or nanometer scales, but they are limited by the low penetration depth, one of the well-known limitations of these methods. 32,33 To address these limitations, PCCT was applied to develop the glioma tissues, which is a label-free, highresolution imaging modality with excellent soft-tissue contrast and superior penetration depth. As expected, the morphology of microvascular proliferation in glioma tissues was clearly observed via PCCT in this study, confirmed by the corresponding histological results.…”
Section: Discussionmentioning
confidence: 99%
“…To date, optical imaging techniques such as confocal laser endomicroscopy (CLE) or ultrastructural methods such as transmission electron microscopy (TEM) have been available for visualizing microstructures in 3D on micrometer or nanometer scales, but they are limited by the low penetration depth, one of the well-known limitations of these methods. 32,33 To address these limitations, PCCT was applied to develop the glioma tissues, which is a label-free, highresolution imaging modality with excellent soft-tissue contrast and superior penetration depth. As expected, the morphology of microvascular proliferation in glioma tissues was clearly observed via PCCT in this study, confirmed by the corresponding histological results.…”
Section: Discussionmentioning
confidence: 99%
“…However, another contributing factor may be LYST-mediated modulation of granules during during the effector response allowing smaller proportions of the large granules to be released, as has been demonstrated for degranulation in mast cells. 79 An outstanding question is how lysosomal fission leads to loss of the granular matrix and granzyme B in hyporesponsive NK cells. Granzyme B can be synthesized and secreted directly through the constitutive secretory pathway.…”
Section: Trpml1-mediated Modulation Of Secretory Granules In Nk Cellsmentioning
confidence: 99%
“…From simple yeast to complex eukaryotic cells. SXT grants an unprecedented contrast and spatial resolution, filling the information gap between light and electron microscopy [33,30,10,5,17,4].…”
Section: Introductionmentioning
confidence: 99%